Sensitivity and specificity of patch test in nickle allergic contact dermatitis - I Ketut Darya Artana, I Ketut Darya Artana (Universitas Gadjah Mada, 1997)
Objectives of the study are as follows: first to compare the sensitivity and specificity of 5.0% nickle sulfate (NS) prepared by Pharmacy Unit Dr. Sardjito General Hospital and 5% NS International standard, and the second is to determine the ideal concentration of NS that can produce equal sensitivity and specificity with 5% NS International standard. Total number of sample is 86 subjects that have been recruited from Dermatology Clinic Sardjito General Hospital. Forty one patients with nickle allergic contact dermatitis and 45 patients with other dermatitis or healthy volunteers participated in the study. Every subject was tested with 5% NS International standard and 5.5%, 5.0%, 4.5%, 4.0%, 3.5%, 3.0%, 2.5%, 2.0% NS made by Pharmacy Unit Dr. Sardjito General Hospital. Result of the study shows that the sensitivity and specificity of 5% NS International standard are 95.12% and 95.56% respectively, while 5.0% NS made by Pharmacy Unit Sardjito General Hospital are 92.68% and 100% respectively (this differences is not statistically significant). Among different concentration of nickle sulfate made by Pharmacy Unit, 2.5% NS is the optimal concentration that can produce sensitivity and specificity which are equal to 5% NS International standard, both on the first and the second assessments (p = 0,06). Conclusion: 2.5% NS patch test made by Pharmacy Unit, Dr. Sardjito General Hospital can be used as standard material patch test for allergic contact dermatitis caused by nickel.Key word: nickle sulfate - pacth test - nickle allergic contact dermatitis.